Review of Penelope Petsini and Dimitris Christopoulos, eds., Λεξικό λογοκρισίας στην Ελλάδα: Καχεκτική δημοκρατία, δικτατορία, μεταπολίτευση : [Dictionary of censorship in Greece: Stunted democracy, dictatorship, metapolitefsi] - Triantafyllou, Christos (Historein, 2022)
Review of Penelope Petsini, Dimitris Christopoulos, eds., Λεξικό λογοκρισίας στην Ελλάδα: Καχεκτική δημοκρατία, δικτατορία, μεταπολίτευση [Dictionary of censorship in Greece: Stunted democracy, dictatorship, metapolitefsi]. Athens: Kastaniotis, 2018. 542 pp. To view the full text, click on the button "HTML".